2016
DOI: 10.21511/ppm.14(3-2).2016.01
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing strategy: how openness changes strategy work

Abstract: Strategy development has traditionally been exclusive and secretive. Social software offers new opportunities to harness the collective intelligence of the crowd within organizations and allows more open, participatory modes of strategizing. This paper describes this new phenomenon of open strategy though crowdsourcing and discusses its implications for research and practice. It draws on first examples of crowdsourcing strategy and is further based on observations and theoretical reflections. To understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This framework also adds to a more detailed understanding about the effects of dilemmas and associated costs of openness (Birkinshaw, 2017;Hautz et al, 2017b) in the different stages of the strategy process. In addition, this study answers recent calls to apply a social network perspective on open strategy (Matzler et al, 2016;Hautz et al, 2017b) and adds to literature on the antecedents of social networks (Borgatti and Foster, 2003;Klein et al, 2004;Borgatti and Halgin, 2011). Finally, it has managerial implications for how organizations should open up their strategy process as it shows that organizations should dynamically vary between different levels of openness and associated open practices across the different strategy phases.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…This framework also adds to a more detailed understanding about the effects of dilemmas and associated costs of openness (Birkinshaw, 2017;Hautz et al, 2017b) in the different stages of the strategy process. In addition, this study answers recent calls to apply a social network perspective on open strategy (Matzler et al, 2016;Hautz et al, 2017b) and adds to literature on the antecedents of social networks (Borgatti and Foster, 2003;Klein et al, 2004;Borgatti and Halgin, 2011). Finally, it has managerial implications for how organizations should open up their strategy process as it shows that organizations should dynamically vary between different levels of openness and associated open practices across the different strategy phases.…”
Section: Introductionmentioning
confidence: 52%
“…Hautz et al (2017b) highlight that the inclusion of these diverse actors is variable and can come in various forms and degrees. Social technologies enable a diversity of open strategy practices such as blogging (Gegenhuber and Dobusch, 2017), Wikis (Dobusch and Kapeller, 2013;Dobusch and Müller-Seitz, 2017), ideation contests and communities (Hutter et al, 2017;Malhotra et al, 2017) or crowdsourcing (Stieger et al, 2012;Matzler et al, 2016). Morton et al (2015) have identified the trend that organizations are increasingly including internal actors, hence employees across departments and hierarchies, independent of experience, tenure or background in the strategy process through these practices (Stieger et al, 2012;Matzler et al, 2016;Hutter et al, 2017).…”
Section: Opening Up the Strategy Processmentioning
confidence: 99%
See 3 more Smart Citations